Medication reconciliation and prescribing reviews by pharmacy technicians in a geriatric ward - Thomas Croft Buck; Louise Smed Gronkjaer; Marie-Louise Duckert; Jens-Ulrik Rosholm; Lise Aagaard (Wolters Kluwer Medknow Publications, 2013)
Objective: Incomplete medication histories obtained on hospital admission are responsible for more than 25% of prescribing errors. This study aimed to evaluate whether pharmacy technicians can assist hospital physicians' in obtaining medication histories by performing medication reconciliation and prescribing reviews. A secondary aim was to evaluate whether the interventions made by pharmacy technicians could reduce the time spent by the nurses on administration of medications to the patients. Methods: This observational study was conducted over a 7 week period in the geriatric ward at Odense University Hospital, Denmark. Two pharmacy technicians conducted medication reconciliation and prescribing reviews at the time of patients' admission to the ward. The reviews were conducted according to standard operating procedures developed by a clinical pharmacist and approved by the Head of the Geriatric Department. Findings: In total, 629 discrepancies were detected during the conducted medication reconciliations, in average 3 for each patient. About 45% of the prescribing discrepancies were accepted and corrected by the physicians. "Medication omission" was the most frequently detected discrepancy (46% of total). During the prescribing reviews, a total of 860 prescription errors were detected, approximately one per medication review. Almost all of the detected prescription errors were later accepted and/or corrected by the physicians. "Dosage and time interval errors" were the most frequently detected error (48% of total). The time used by nurses for administration of medicines was reduced in the study period. Conclusion: This study suggests that pharmacy technicians can contribute to a substantial reduction in medication discrepancies in acutely admitted patients by performing medication reconciliation and focused medication reviews. Further randomized, controlled studies including a larger number of patients are required to elucidate whether these observations are of significance and of importance for securing patient safety.